Analisis Cemaran Bakteri Coliform pada Saus Jajanan di Sekitar Sekolah Menengah Kejuruan di Kota Medan - Lisda Mayanti; Yayuk Putri Rahayu; Minda Sari Lubis; Rafita Yuniarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The sauce is a type of food additive prepared from the main ingredients of chilies and tomatoes, served as a complement to food and often served in snack foods. Nowadays, sauces are in great demand by all groups, but many traders need to pay more attention to their wares, both in terms of presentation and how to process them, for example diluting sauces with unclean water so they are contaminated with pathogenic microbes. One form of biological contamination that can occur in the sauce is the presence of coliform bacteria. This group of coliform bacteria includes Escherichia coli (E. coli), Gram-negative bacteria that are rod-like and do not form spores. Normally, E. coli is part of the normal intestinal flora, but it can cause illnesses such as diarrhea when opportunistic. The purpose of this study was to test the level of bacterial contamination as measured by the Total Plate Count (ALT), as well as to determine the presence of coliform bacteria and identify E. coli bacteria in the sauces used in various types of snacks around SMKs in the city of Medan. Methods The research approach involves the use of two methods, namely the Total Plate Number (ALT) and the Most Probable Number (MPN). Based on the determination of the value of ALT < 1 x104 coli/g and MPN < 100/g. The results of the study from 5 samples of various snack sauces around one of Medan City Vocational Schools were not suitable for consumption because they did not meet SNI No.7388:2009 with the amount of microbial contamination in chili sauce that is above 1x10⁴ colonies/g and exceeding the maximum MPN coliform limit in chili sauce, i.e., above 100 colonies/g.